2020
DOI: 10.1016/j.heliyon.2020.e04983
|View full text |Cite
|
Sign up to set email alerts
|

Income level and healthcare utilization in Calabar Metropolis of Cross River State, Nigeria

Abstract: Throughout the world, socio-economic status differentials of individuals have a lot of influence on privileges and opportunities enjoyed by society members. The different social and economic positions of individuals and income levels oftentimes hinder them from effective use of health care facilities. It is against this background, that the study was designed to investigate income differentials and its influence on utilization of healthcare services among the people of Calabar Metropolis in Cross River State, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Concerning the intended use of medical care, income was the only influential factor in enabling resources. This finding provided further evidence that poor income can be a hindrance to health seeking and the utilization of care services [ 15 , 31 ]. However, the intended use of medical care was not influenced by other factors of the enabling resources.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Concerning the intended use of medical care, income was the only influential factor in enabling resources. This finding provided further evidence that poor income can be a hindrance to health seeking and the utilization of care services [ 15 , 31 ]. However, the intended use of medical care was not influenced by other factors of the enabling resources.…”
Section: Discussionmentioning
confidence: 85%
“…The predisposing characteristics of age, gender, and education level were found to be significant predictors [ 12 , 13 ]. Moreover, enabling resources (such as marital status, living arrangements, and income) were reported to be associated with older adults’ needs [ 14 , 15 ]. In addition, physical health status, as the need factor, also strongly impacts older adults’ demand for care services [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…19 People with better economic groups can get better health services than people in low economic groups. 20 Socioeconomic factors will influence the decision-making and individual behavior to obtain good health services. 21 Several studies have shown that countries with low economic capacity will affect individuals to pay for health services.…”
Section: Discussionmentioning
confidence: 99%
“…In a typical Nigerian village, majority of the population comprises old people who are mostly economically unproductive due to ill health brought about by ageing (Anele, 2012). According to Archibong et al (2020), individuals with low financial capacity and socio-economic status anywhere in the world are exposed to and defenceless against a great deal of health risks. Many times, the rural aged in Nigeria have low income and no access to benefits covering the costs of medications and therefore go without or spend a large part of their incomes on medications.…”
Section: Introductionmentioning
confidence: 99%